Potential lipid-based strategies of amphotericin B designed for oral administration in clinical application - Xiaoming Zhong; Jianqiong Yang; Hongyan Liu; Zhiwen Yang; Ping Luo (Taylor & Francis Group, 2023)
AbstractAmphotericin B (AmB) is regarded as a first-line therapy against life-threatening invasive fungal infections. Due to its poor oral bioavailability, AmB is restricted to intravenous administration in clinical practice. As science continues to move forward, two lipid-based formulations are successfully developed for oral AmB administration, currently undergoing phase I clinical trials. Encouragingly, lipid-AmB conjugates with emulsions also exhibit a better bioavailability, which may be another strategy to design oral AmB formulation in clinical practice. Thus, this review mainly focused on the two lipid-based formulations in clinical trials, and discussed the potential perspectives of AmB-lipid conjugation-loaded nanocochleates and emulsions.